2020
DOI: 10.1080/23802359.2020.1742612
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete mitochondrial genome of the praying mantis Rhombodera longa (Mantodea: Mantidae) including a phylogenetic analysis

Abstract: The complete mitochondrial genome of Rhombodera longa Yang, 1997 was sequenced in this study (GenBank accession no. MT110155). This molecule is circular in shape with 15,886 bp length, containing 13 protein-coding genes (PCGs), 2 ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes, and a non-coding control region. The AT content of the whole genome is 76.1% and the length of the control region is 636 bp with 78.2% AT content. This gene arrangement is consistent with the mitochondrial genomes of other pray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…In an attempt to address the phylogenetic relationships with Gonypetidae and Haaniidae, 69 previous mantises mitogenomes, downloaded from NCBI, as well as nine newly combined mitogenomes, were selected as ingroups [ 6 , 7 , 8 , 10 , 11 , 21 , 22 , 29 , 30 , 39 , 44 , 66 , 67 , 68 , 69 , 70 ] ( Table S1 ). Two cockroach species, Eupolyphaga sinensis and Cryptocercus kyebangensis , and two termites, Termes hospes and Macrotermes barneyi , were chosen as outgroup taxa [ 71 , 72 , 73 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to address the phylogenetic relationships with Gonypetidae and Haaniidae, 69 previous mantises mitogenomes, downloaded from NCBI, as well as nine newly combined mitogenomes, were selected as ingroups [ 6 , 7 , 8 , 10 , 11 , 21 , 22 , 29 , 30 , 39 , 44 , 66 , 67 , 68 , 69 , 70 ] ( Table S1 ). Two cockroach species, Eupolyphaga sinensis and Cryptocercus kyebangensis , and two termites, Termes hospes and Macrotermes barneyi , were chosen as outgroup taxa [ 71 , 72 , 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…These species are distributed worldwide, mainly in tropical and subtropical areas, and occupy diverse habitats ranging from tropical rainforests to arid deserts [ 2 , 3 ]. There have been numerous studies exploring the taxonomic status within Mantodea based on morphology or molecular data [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Existing research confirmed the monophyly of the order Mantodea and Mantodea clustered into Dictyoptera with Blattodea [ 4 , 17 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…All specimens were immediately placed in absolute alcohol and stored at −20℃ until DNA extraction. All species were identified through morphological keys (Beier, 1933; Liu et al, 2021; Wang 1995; Wang, Cheng, et al, 2020; Zhang & Li, 1983) and with DNA barcoding (Bold Systems v4, http://www.boldsystems.org/). Total genomic DNA was extracted from the muscle tissue of single individuals using the TIANamp Genomic DNA kit (Tiangen Biotech) following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Mitogenome is a useful marker for resolving phylogenetic relationships among Mantodea (Zhang & Ye, 2017). As of October 2021, only 32 complete/nearly complete mitogenomes of Mantidae have been sequenced (Cameron et al, 2006; Tian et al, 2015; Wang et al, 2020a; Xu et al, 2021; Ye et al, 2016; Zhang & Ye, 2017; Zhang et al, 2018b). Additional mitogenome data from Mantidae will contribute to our phylogenetic understanding within the family.…”
Section: Introductionmentioning
confidence: 99%